Abnormalities on structural MRI associate with faster disease progression in multiple system atrophy. (January 2019) - Krismer, Florian; Seppi, Klaus; Wenning, Gregor K.; Papapetropoulos, Spyridon; Abler, Victor; Goebel, Georg; Schocke, Michael; Poewe, Werner
Abstract: Background: The rate of clinical progression in patients with multiple system atrophy (MSA) varies between individuals and predictors for disease progression remain undefined. While the MSA-rasagiline study found no difference in the rates of clinical progression for patients treated with rasagiline versus placebo, it included a large, prospective magnetic resonance imaging (MRI) substudy that can provide new information on the underlying disease progression in patients with early MSA. Methods: This post-hoc analysis compared the rate of clinical progression in patients with MSA-specific structural changes at baseline (MRI-positive group) versus the rate of progression in patients without evidence of such changes at baseline (MRI-negative group) using a repeated measures ANCOVA. Clinical progression was assessed using the Unified MSA Rating Scale (UMSARS) and Clinical Global Impression of Improvement (CGI-I). Results: Twenty-eight patients with early MSA of the parkinsonian subtype (MRI-positive n = 13; MRI-negative n = 15) who had complete baseline and follow-up UMSARS data were included in this analysis. Patients in the MRI-positive group had faster clinical progression from baseline to the end of the 48-week study compared with those in the MR-negative group as assessed by the UMSARS total (p = 0.028) and UMSARS motor (p = 0.008) scales. At week 48, MRI-positive patients also had a significantly worse health status vs. MRI-negative patients (p = 0.015). Conclusions: This is the first study to demonstrate that MSA-specific abnormalities on structural MRI might represent a variant of MSA-P that is associated with more rapid progression and an overall worse prognosis. Highlights: MSA-specific MRI abnormalities associate with faster disease progression in multiple system atrophy. Incorporating MRI into trial design will reduce the number of patients required to show an effect. An understanding of the differing rates of progression will aid in the planning of long-term care.